Application of toll-like receptors (TLRs) and their agonists in cancer vaccines and immunotherapy - Chakraborty, Samik; Ye, Juan; Wang, Herui; Sun, Mitchell; Zhang, Yaping; Sang, Xueyu; Zhuang, Zhengping (Frontiers in Immunology, 2023)
Toll-like receptors (TLRs) are pattern recognition receptors (PRRs) expressed in various immune cell types and perform multiple purposes and duties involved in the induction of innate and adaptive immunity. Their capability to propagate immunity makes them attractive targets for the expansion of numerous immunotherapeutic approaches targeting cancer. These immunotherapeutic strategies include using TLR ligands/agonists as monotherapy or combined therapeutic strategies. Several TLR agonists have demonstrated significant efficacy in advanced clinical trials. In recent years, multiple reports established the applicability of TLR agonists as adjuvants to chemotherapeutic drugs, radiation, and immunotherapies, including cancer vaccines. Cancer vaccines are a relatively novel approach in the field of cancer immunotherapy and are currently under extensive evaluation for treating different cancers. In the present review, we tried to deliver an inclusive discussion of the significant TLR agonists and discussed their application and challenges to their incorporation into cancer immunotherapy approaches, particularly highlighting the usage of TLR agonists as functional adjuvants to cancer vaccines. Finally, we present the translational potential of rWTC-MBTA vaccination [irradiated whole tumor cells (rWTC) pulsed with phagocytic agonists Mannan-BAM, TLR ligands, and anti-CD40 agonistic Antibody], an autologous cancer vaccine leveraging membrane-bound Mannan-BAM, and the immune-inducing prowess of TLR agonists as a probable immunotherapy in multiple cancer types.